Ensiklopedi Rumah Adat di Pulau Jawa Menggunakan Teknologi Augmented Reality sebagai Media Pembelajaran yang Interaktif - Wijaya Wahyudi Akbar; Oky Dwi Nurhayati; Kurniawan Teguh Martono (Jurnal Teknologi dan Sistem Komputer, 2015)
Technological advances become one of the important moments in human life, because the technology effect on all areas related to human. Both in the military, health, community services, education, and much more. Education is the key factor in the progress of a nation. Education that is integrated with the technological advances of course be one of the driving force of the nation's progress. One of them using augmented reality technology. Applications Java Encyclopedia Traditional House is the result of the combined two essential components, namely education and technology. Using augmented reality-based technology that can facilitate learning in a familiar custom home on the island of Java. There are 6 custom homes in every province of the island of Java, namely kebaya in jakarta, kesepuhan Cirebon in West Java, East Java situbondo, Padepokan in Central Java, Badui in Banten, and Kencono Traditional House in Yogyakarta. Applications built using the C # programming language, it is very interactive. So that users not only know the 3-dimensional shape of an existing custom home, but know many things about the area tersebut.Telah conducted testing of these applications, functionally works well and reading the marker successfully.